2009
DOI: 10.1016/j.bone.2009.02.010
|View full text |Cite
|
Sign up to set email alerts
|

EP2 and EP4 receptors differentially mediate MAPK pathways underlying anabolic actions of prostaglandin E2 on bone formation in rat calvaria cell cultures

Abstract: Of the four prostaglandin (PG) E receptor subtypes (EP1-EP4), EP2 and EP4 have been proposed to mediate the anabolic action of PGE(2) on bone formation but comparative evaluation studies of EPs on bone formation do not necessarily share a common mechanism, implying that their additional features including downstream MAPK pathways may be beneficial to resolve this issue. We systematically assessed the roles of EPs in the rat calvaria (RC) cell culture model by using four selective EP agonists (EPAs). Consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 65 publications
2
55
1
2
Order By: Relevance
“…Eicosanoids are known to be local regulators of bone metabolism (37). Some pathways sustaining the anabolic action of prostaglandin EP2 and EP4 receptors have been recently uncovered (38). Our unpublished results indicate that EP4 receptors are induced along the osteogenic differentiation of C1 cells.…”
Section: Discussionmentioning
confidence: 48%
“…Eicosanoids are known to be local regulators of bone metabolism (37). Some pathways sustaining the anabolic action of prostaglandin EP2 and EP4 receptors have been recently uncovered (38). Our unpublished results indicate that EP4 receptors are induced along the osteogenic differentiation of C1 cells.…”
Section: Discussionmentioning
confidence: 48%
“…In contrast, findings from in vitro studies utilizing hMSCs derived from bone marrow and adipose tissue suggest that PGE 2 may also have a negative influence on osteogenesis (10,19). Our findings showed that continuous treatment with showing that bone formation is enhanced by a selective EP agonists (24)and also that PGE 2 -mediated bone formation is abolished only in EP2 or EP4 knockout mice (25,26). It also suggested that PGE 2 mediated its effects through EP2 and EP4 in inhibiting matrix mineralization of hMSCs derived from bone marrow (10).…”
Section: Pge 2 Receptor Gene Expressioncontrasting
confidence: 51%
“…Two intracellular enzymes known to be downstream of PGE 2 ā†’EP2 signaling, PKA (82) and p38 MAPK (83)(84)(85)(86), have a prior demonstrated role in promoting AID mRNA expression. Thus, PKA and downstream CREB were reported to promote IL-4-driven, STAT6-dependent AID mRNA in mouse B cells (87); in addition, p38 MAPK was found necessary for BAFF synergy with IL-4 in promoting AID mRNA synthesis in human B cells (88).…”
Section: Discussionmentioning
confidence: 99%